Evaluation of the Futsal Coaching Program at the Palu City Futsal Association - Marco Marco; Nasuka Nasuka; Agung Wahyudi (STKIP Muhammadiyah Kuningan, 2023)
The objectives of this study: (1) Evaluating the context of the coaching program, including background, AD/ART, Vision-Mission, and objectives of the coaching program; (2) Evaluating the input of the coaching program, including human resources, facilities, and infrastructure and funding sources, (3) Evaluating the program process, including the Coach Admission System, the Athlete Admission System, the Use of Facilities and Infrastructure, coordination and consumption; (4) Evaluate the product of achievement and welfare coaching programs. This research uses a context, input, process, and product evaluation model that produces comprehensive final information on the futsal coaching program. The source of this research is the administrators, coaches, and futsal athletes of AFKOT. Data collection techniques with observation, in-depth interviews, documentation, and data triangulation. The data obtained are analyzed qualitatively with the following scarcity: (1) data reduction, (2) data presentation, and (3) conclusion. The results of this study show that; (1) The context of the background futsal coaching program, AD / ART, Vision and Mission, and objectives of the futsal coaching program is suitable for AFKOT; (2) The input of the AFKOT program has good human resources, the feasibility of facilities and infrastructure is excellent, and the source of funds that still has limitations: (3) The process of implementing the training program is the right of the coach, but there is input from the management because the management is also involved in recruitment. Transportation and coordination have been very well carried out in AFKOT. (4) The product of the futsal coaching program is for futsal achievements in Palu City to be good but to defend the champion is still not stable in 2019-2022. The conclusion of this study is whether the context, input, and process are good. At the same time, in the Palu City futsal product, the achievements have been exemplary because Palu City often participates in Indonesian futsal championships, but defending the champion is still unstable.